Impact of EGFR inhibitor in non-small cell lung cancer on progression-free and overall survival: A meta-analysis - Chee Khoon Lee (2018)
Background The epidermal growth factor receptor (EGFR) signaling pathway is crucial for regulating tumorigenesis and cell survival and may be important in the development and progression of non-small cell lung cancer (NSCLC). We examined the impact of EGFR-tyrosine kinase inhibitors (TKIs) on progression-free survival (PFS) and overall survival (OS) in advanced NSCLC patients with and without EGFR mutations.MethodsRandomized trials that compared EGFR-TKIs monotherapy or combination EGFR-TKIs-chemotherapy with chemotherapy or placebo were included. We used published hazard ratios (HRs), if available, or derived treatment estimates from other survival data. Pooled estimates of treatment efficacy of EGFR-TKIs for the EGFR mutation-positive (EGFRmut + ) and EGFR mutation-negative (EGFRmut - ) subgroups were calculated with the fixed-effects inverse variance weighted method. All statistical tests were two-sided.ResultsWe included 23 eligible trials (13 front-line, 7 second-line, 3 maintenance; n = 14570). EGFR mutation status was known in 31% of patients. EGFR-TKIs treatment prolonged PFS in EGFRmut + patients, and EGFR mutation was predictive of PFS in all settings: The front-line hazard ratio for EGFRmut + was 0.43 (95% confidence interval [CI] = 0.38 to 0.49; P < . 001), and the front-line hazard ratio for EGFRmut - was 1.06 (95% CI = 0.94 to 1.19; P =. 35; P interaction < . 001). The second-line hazard ratio for EGFRmut + was 0.34 (95% CI = 0.20 to 0.60; P < . 001), and the second-line hazard ratio for EGFRmut - was 1.23 (95% CI = 1.05 to 1.46; P =. 01; P interaction < . 001). The maintenance hazard ratio for EGFRmut + was 0.15 (95% CI = 0.08 to 0.27; P < . 001), and the maintenance hazard ratio for EGFRmut - was 0.81 (95% CI = 0.68 to 0.97; P =. 02; P interaction < . 001). EGFR-TKIs treatment had no impact on OS for EGFRmut + and EGFRmut - patients.ConclusionsEGFR-TKIs therapy statistically significantly delays disease progression in EGFRmut + patients but has no demonstrable impact on OS. EGFR mutation is a predictive biomarker of PFS benefit with EGFR-TKIs treatment in all settings. These findings support EGFR mutation assessment before initiation of treatment. EGFR-TKIs should be considered as front-line therapy in EGFRmut + advanced NSCLC patients. © 2013 The Author.